2021
DOI: 10.30919/es8d1158
|View full text |Cite
|
Sign up to set email alerts
|

Conversions of Waste Tube-Tyres (WTT) and Waste Polypropylene (WPP) into Diesel Fuel through Catalytic Pyrolysis Using Base SrCO3

Abstract: Diesel fuels obtained from waste tube-tyre (WTT) and waste polypropylene (WPP) were found using the base strontium carbonate (SrCO3) as a catalyst through a catalytic-pyrolysis cracking. Liquid hydrocarbons fuels were analyzed through GC-MS-MS, FT-IR, 1 H and 13 C NMR, ICP. Physicochemical properties of diesel fuel were analyzed through ASTM methods. Their results were found such as saturates, naphthenes, aromatics, monohydric alcohols, aldehydes, esters, amides, halides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…The major products were aromatics, naphthenes, monohydric alcohols, esters, amides, and halides. Diesel fuel from WTT and WPP has research octane numbers of 89.65 and 87.32, respectively [ 80 ].…”
Section: Waste Plastic Recycling and Technologymentioning
confidence: 99%
“…The major products were aromatics, naphthenes, monohydric alcohols, esters, amides, and halides. Diesel fuel from WTT and WPP has research octane numbers of 89.65 and 87.32, respectively [ 80 ].…”
Section: Waste Plastic Recycling and Technologymentioning
confidence: 99%
“…In recent years, functional materials derived from waste have been developed to substitute synthetic materials. Waste-based materials with diverse microstructures and desirable surface properties are the focus of much attention not only as environmentally friendly materials for ecological protection but also as advanced materials with excellent properties for various applications, such as using fluorescent carbon dots produced from single-use plastic cups and conversions of waste tube tyres and waste polypropylene into diesel fuel through catalytic pyrolysis. To date, a series of solid wastes for the fabrication of functional materials are investigated. For instance, Tian et al reported an industrial sludge-derived multifunctional layer for complex oily wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Waste tire rubber in particular has gained a significant research interest owing to the abundant availability. Furthermore, the land fill burden and disposal issues concerning waste tire rubber has made the researchers all around the globe to look for feasible ways to tackle the problems [25][26][27][28][29]. Tires used for automobiles and airplanes are disposed after attaining their life cycle and thus heaps of tires are piled up creating abundant disposal issues [30].…”
Section: Introductionmentioning
confidence: 99%